Lamellar Dissection Technique for Descemet Membrane Endothelial Keratoplasty Graft Preparation. Issue 1 (January 2020) - Tan, Tien-En; Devarajan, Kavya; Seah, Xin-Yi; Lin, Shu-Jun; Peh, Gary Swee Lim; Cajucom-Uy, Howard Yu; Ang, Marcus Han Nian; Tan, Donald Tiang Hwee
Abstract : Purpose: To describe a novel lamellar dissection technique for Descemet membrane endothelial keratoplasty (DMEK) graft preparation, and to evaluate the rate of endothelial cell loss (ECL) and graft preparation failure associated with this technique. Methods: We conducted an ex vivo laboratory-based study comparing ECL between the lamellar dissection and peeling techniques. Eight pairs of human donor corneas underwent calcein acetoxymethyl staining—all right eyes underwent the peeling technique and all left eyes underwent the lamellar dissection technique. ECL was quantified by image analysis with trainable segmentation software and compared between groups. We also conducted a retrospective analysis of 161 consecutive DMEK graft preparations by a single surgeon using the lamellar dissection technique from 2010 to 2018. Data on donor characteristics and graft preparation failures were obtained. Results: Baseline donor characteristics were comparable in both arms of the laboratory-based study. Mean (SD) ECL with the lamellar dissection and peeling techniques was 13.8% (4.2%) and 11.2% (6.1%), respectively. There was no significant difference between the two ( P = 0.327). In the clinical series, there were 2 graft preparation failures in 161 cases (1.2%). Among cases performed on diabetic donor tissue, the rate of graft preparation failure was 4.7%. Conclusions: The lamellar dissection technique has a similar rate of ECL compared with the peeling technique for DMEK graft preparation. This technique also has a low rate of graft preparation failure and may be a useful technique for diabetic donor tissue. Abstract : Supplemental Digital Content is Available in the Text.